PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) DALAM PELAKSANAAN PEMBANGUNAN DI KELURAHAN WATONEA KECAMATAN KATOBU KABUPATEN MUNA - Sitti Rahmatyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the role of community empowerment institutions (LPM) in implementing development in Watonea Village Katobu District, Muna Regency. Data collected from the results of the research were selected and then analyzed descriptively qualitatively using quantitative data. Qualitative descriptive is intended to obtain a description of various kinds of data according to the variables or indicators that have been determined and explained, then tabulated in the form of percentages. The results show that the role of community empowerment institutions (LPM) in the development of Watonea is a role in compiling participatory development plans, roles in mobilizing self-help and mutual cooperation, implementing roles and controlling development